Essential prescribing tips for GP Associates-in-Training. Issue 2 (February 2018) - Gookey, Gill; Knox, Richard; Salema, Nde-Eshimuni; Marsden, Kate; Bell, Brian; Bassi, Mindy; Silcock, Nick; Swanwick, Glen; Avery, Anthony
Prescribing is an essential role in general practice but it is also, at times, a high risk activity. GP Associates-in-Training (GP AiTs) have been highlighted as needing further support to reduce the risk of prescribing errors. This article highlights some common prescribing errors to help GP AiTs to review their prescribing and develop prescribing habits to avoid errors. The general practice workforce is changing and there are more pharmacists working in general practice. This article describes the role of clinical pharmacists in prescribing safety and in supporting GP AiTs.